What is walkability? The urban DMA. (January 2020) - Dovey, Kim; Pafka, Elek
The concept of urban 'walkability' has come to occupy a key role at the nexus of a series of multidisciplinary fields connecting urban design and planning to broader issues of public health, climate change, economic productivity and social equity. Yet the concept of walkability itself remains elusive – difficult to define or operationalise. Density, functional mix and access networks are well-recognised as key factors: density concentrates more people and places within walkable distances; functional mix produces a greater range of walkable destinations; and access networks mediate flows of traffic between them. This complex synergy of density, mix and access – herein called the urban DMA – largely stems from the work of Jacobs. With an approach based in assemblage thinking we show that each of these factors is multiple and problematic to define or measure. Any reduction to a singular index of morphological properties can involve a misrecognition of how cities work. We argue that walkability is a complex and somewhat nebulous set of capacities embodied in any urban morphology, and that it should not be conflated with nor derived from actual levels of walking.